(untitled) - Mair, Andrew (New York, NY, 1994)
The Japanese Firm Goes Global ; A 'Self-Reliant Motor Vehicle Company' in North America ; Fortress Europe: Inside the Walls...
Keywords: Quản lý công nghiệp,Industrial management